Dissemination of Infectious Diseases Significant for the Sanitary Protection of the Territory of the Russian Federation in East-Mediterranean Region - A. E. Shiyanova; S. K. Udovichenko; L. N. Dmitrieva; A. V. Ivanova; V. P. Toporkov; E. V. Kouklev; A. V. Boiko (Проблемы особо опасных инфекций, 2017)
Objective of the study is to generalize epidemiological data and assess the situation in the countries of East-Mediterranean region on infectious diseases that require the measures on sanitary protection of the territory of the Russian Federation, CIS member-states, and Eurasian Economic Union. Materials and methods. Epidemiological analysis was carried out using the data of official websites and periodical publications of WHO, WHO East-Mediterranean Office, National Health Ministries, Center for Disease Control and Prevention, other international organizations and open-access literature sources. Results and conclusions. Systematized and summarized have been the data on morbidity rates and spatial dissemination of diseases in each particular country from the point of view of possible risks to visiting them individuals. The data presented on the infectious diseases allow for addressing the issues associated with the risk of infection; identification of the factors and terms of high risk of infection; for forecasting the probability of disease importation into the Russian Federation. The information may prove to be useful for quantitative and qualitative evaluation of potential epidemic hazard in the course of sanitary-epidemiological welfare provision under international mass events.